A Brief Hope Intervention to Increase Hope Level and Improve Well-Being in Rehabilitating Cancer Patients: A Feasibility Test. (May 2019) - Chan, Kitty; Wong, Frances K. Y.; Lee, Paul H.
This article reports on the feasibility and effect of the brief hope intervention (BHI) in terms of increasing the hope level and psychological and physical health outcomes of rehabilitating cancer patients (RCP). Chinese RCP living in the community were invited to join the study. The BHI consisted of four one-on-one sessions: two (1-hour) face-to-face sessions and two (30-minute) telephone follow-up sessions in between. There were three core features in the hope therapy: (a) goal thoughts: finding workable goals, (b) pathway thoughts: finding ways to reach the targets, and (c) agency thoughts: positive self-talk to optimize their motivation to accomplish the set goals. A one-group pre- and postintervention design was used. Outcome measures included the Memorial Symptom Assessment Scale, the Center for Epidemiological Studies Depression Scale (CES-D), and the State Hope Scale. Recruitment, attrition, and qualitative feedback were collected to understand their comments on BHI. A total of 40 participants were recruited (female 92.3%). The mean age was 57.2 years ( SD  = 6.7). The participants had significant improvement in all aspects of the Memorial Symptom Assessment Scale, with moderate-to-large effect sizes ( d  = 0.49–0.74). The changes in present hope and depression scores were insignificant, with small effect sizes ( d  = 0.17–0.34). The BHI seemed to be promising in producing both physical and psychological benefits in RCP